Manejo de residuos sólidos del ámbito municipal del distrito de Cacatachi - Torres Torres, Luis Miguel (2011)
This Graduate Research Protect is an assessment of the current situation facing the Solid Waste Management in the city of San Martiri Cacatachi "Province, Department of the same name, in the sense we give our small modest contribution for of solid Waste management in the Peruvian jungle, and the currently the area mountains and forest of our country has not yet internalized the concepts in all seriousness local governments that currently manages hedge fund are attractive municipal economically disadvantaged by the Law on Decentralization and the transfer Act witch empowers then and powers as regards political autonomy, economic administrative, despite all this we have failed to prioritize development projects and of great interest of community, in this sense that gives a warning to local and regional leaders in our interest to give priority in funding a basic sanitation projects as appropriate specific case management system solid Waste municipal authority which is the core interest of this thesis final report carried in the town of Cacatachi 201 O. On my not going to allow improving the operational part of the whole life cycle of waste produced in the urban part of the town of Cacatachi. The information generate is related to output per capita per day, physical composition of solid waste and all information regarding the interests of design and build a sanitary landfill to see if anything together to attach it to a centralized landfill would be located in district Yacucatina Juan Guerra, the same not only recepcionaría Cacatachi municipal waste but also from neighboring districts and moral, Cuñumbuqui, Lamas, Tarapoto, Morales, La Banda de Shilcayo and Juan Guerra. for community, in this